Transcriptome Sequencing Reveals Potential Roles of ICOS in Primary Sjögren’s Syndrome - Luo, Jing; Liao, Xin; Zhang, Lihe; Xu, Xin; Ying, Senhong; Yu, Mengjiao; Zhu, Lixia; Lin, Suxian; Wang, Xiaobing (Frontiers in Cell and Developmental Biology, 2020)
Primary Sjögren’s syndrome (pSS) is a chronic systemic autoimmune disease characterized by exocrine glands damage and extraglandular involvements. To identify potential biomarkers for the early detection of pSS and to further investigate the potential roles of the biomarkers in the progression of pSS, our previous RNA-sequencing data and four microarrays data of salivary glands (SGs) were combined for integrative transcriptome analysis between pSS and non-pSS. Differential gene expression analysis, gene co-expression network analysis and pathway analysis were conducted to detect hub genes, which was subsequently investigated in peripheral blood mononuclear cell (PBMC) and plasma. Correlation analysis, single-gene Gene Set Enrichment Analysis (GSEA) and receiver operating characteristic (ROC) curve were applied to investigate the potential function of the hub genes and its classification capacity for pSS. A total of 51 common up-regulated genes were identified among different pSS cohorts. A key module was found to be the most closely linked to pSS, which was significantly associated with inflammation-related pathways. Seven overlapped hub genes (ICOS, SELL, CR2, BANK1, MS4A1, ZC3H12D, CCR7) were identified, among which ICOS was demonstrated to involve in most crucial immune pathways. ICOS was up-regulated not only in SGs but also in PBMC and plasma in pSS and the expression of ICOS was closely associated with lymphocytic infiltration in SGs and disease activity of pSS patients. It showed strong classification capacity with classic clinical index in SGs (ROC curve 0.9821) and significant distinct discrimination in PBMC (ROC curve 0.9107). These findings are expected to gain a further insight into the pathogenesis of pSS and provide a promising candidate for early detection of pSS.